Assessing Farmer Incentives for Transitioning Toward Sustainable Agriculture and Provisioning of Clean Water - Ryan, Benjamin E. K.; Shrum, Trisha; Zia, Asim (Frontiers in Water, 2022)
Farms are a major source of water pollution in the form of nutrient run off that cause harmful algal blooms and anoxia, both signs of deteriorating water quality. Current policies that incentivize the adoption of nutrient management practices (NMPs) are insufficient, especially as climate change increases the frequency and intensity of flooding. To evaluate the incentives of current policy designs, we implemented a conjoint analysis on survey data collected in the Missisquoi and Lamoille watersheds of Lake Champlain Basin in three waves (2013, 2015, 2020). Using panel and cross-sectional observations over the three waves, we investigate farmers' willingness to accept (WTA) payment for NMPs that improve soil health and reduce nutrient runoff. We identified farmers' WTA for the adoption of three NMPs, cover cropping, conservation tillage, and buffer strips. The approach quantifies gaps between the incentives offered by the current federal conservation programs and payments preferred by farmers as well as the relative importance of NMP attributes. The influence of the payments decreased over the course of the three survey waves, suggesting the characteristics of NMPs are driving farmers’ preferences for them. Our analysis shows farmers WTA is 1.13 - 6 times higher than what existing incentive programs offer. The incentive gaps between WTA and the cheapest of NMPs offered by EQIP are $55.61 for tillage, $103.60 for cover crop and $37.62 for buffers. Designing policy instruments to reduce this gap, the federal programs and policies will be more effective at scaling up the adoption of NMPs by farmers as a tool for sustainable watershed management.